2007
DOI: 10.1086/520666
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak Management and Implications of a Nosocomial Norovirus Outbreak

Abstract: Background. Noroviruses are enterically transmitted and are a frequent cause of gastroenteritis, affecting 23 million people annually in the United States. We describe a norovirus outbreak and its control in a tertiary care hospital during February-May 2004.Methods. Patients and health care workers met the case definition if they had new onset of vomiting and/or diarrhea during the outbreak period. Selected stool samples were tested for norovirus RNA. We also determined outbreak costs, including the estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
142
0
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 22 publications
(29 reference statements)
2
142
0
9
Order By: Relevance
“…Norovirus is spread rapidly in environments where people are found in close proximity, including schools and daycare centers, nursing homes, cruise ships, and hospitals. Importantly, hospital outbreaks can result in significant economic damage, with direct and indirect costs from a single outbreak reaching $650,000 (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Norovirus is spread rapidly in environments where people are found in close proximity, including schools and daycare centers, nursing homes, cruise ships, and hospitals. Importantly, hospital outbreaks can result in significant economic damage, with direct and indirect costs from a single outbreak reaching $650,000 (4).…”
mentioning
confidence: 99%
“…Studies of antigenic variation in GII. 4 norovirus have shown that the P2 region is involved in strain-specific antibody recognition (7,11,12) and contains at least three blockade (potential neutralization) epitopes (13)(14)(15). In epidemic strains, genetic variation in P2 is linked to antigenic changes over time, indicating that molecular evolution in the P2 subdomain is likely driven by escape from human herd immunity (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Strain MD2004-3 was identified in 2004 as a causative agent of diarrhea in a Baltimore, MD, hospital outbreak (29). This strain grouped within the Farmington Hills cluster of the GII.4 genotype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial resistance may also evolve or be acquired in the community and be introduced into a health care facility from the community, where the infection can spread widely. [1][2][3][4][5][6] The suggestions presented in this review provide a basic approach that can be applied to prevent the transmission of current antimicrobial-resistant pathogens and those that may arise in the future.…”
mentioning
confidence: 99%
“…Although these suggestions are based on meta-analysis of an extensive number of reports and intervention studies, they are resource intensive and are, thus, impractical and unrealistic in the home. 4,5,12 Within the home, the concern about antimicrobial-resistant microorganisms, such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus and Clostridium difficile, in addition to Mycobacterium tuberculosis and respiratory and gastrointestinal viruses, relates to the implications for the patient and other people living with or visiting people infected or colonized with these pathogens, 1,11,12,[21][22][23][24][25][26][27][28] as well as to home-based health care providers. The true prevalence and risk of transmission of MRSA, vancomycin-resistant Enterococcus, extended spectrum β-lactamase-producing gram negative bacteria, Acinetobacter baumanii and C. difficile in the community among patients, their caregivers and family members is not known.…”
mentioning
confidence: 99%